Machining performance of TiN coatings incorporating indium as a solid lubricant - Guleryuz, Canan G.; Krzanowski, James E.; Veldhuis, Stephen C.; Fox-Rabinovich, German S. (Surface & coatings technology, 2009)
The machining and wear performance of TiN-coated and patterned carbide inserts incorporating indium as a solid lubricant are reported in this study. Cutting tests were conducted by turning hardened 4340 steel in both lubricated and dry conditions. During turning, periodic flank wear measurements were made. The chips formed during cutting were examined by scanning electron microscopy, as the condition of the chip reflects the conditions obtained during machining. Inserts subject to dry machining were also examined using optical microscopy and X-ray photoelectron spectroscopy to determine the extent of damage on the rake surface as well as the degree of material transfer. The results showed indium to be effective in reducing flank wear during lubricated machining, but little additional benefit of patterning was observed. For dry machining, some degree of improvement was noted in the patterned sample, but the degree of lubricity brought about by the indium coating was not sufficient and the overall flank wear was higher than the lubricated tests. However, the wear and damage on the rake surface along the path of the chip was reduced by the presence of the In-containing microreservoirs. An additional test was conducted using an instrument that simulates temperature effects during machining, and it was found that the lubricity achieved by In coatings is lost above 450 °C. These results suggest that the use of indium is limited to below this temperature, and above this temperature transforms to a less lubricious indium oxide.